Nutrient-mediated modulation of flowering time - Zhang, Yuhang; Liu, Baohui; Kong, Fanjiang; Chen, Liyu (Frontiers in Plant Science, 2023)
Nutrition affects plant growth and development, including flowering. Flowering represents the transition from the vegetative period to the reproduction period and requires the consumption of nutrients. Moreover, nutrients (e.g., nitrate) act as signals that affect flowering. Regulation of flowering time is therefore intimately associated with both nutrient-use efficiency and crop yield. Here, we review current knowledge of the relationships between nutrients (primarily nitrogen, phosphorus, and potassium) and flowering, with the goal of deepening our understanding of how plant nutrition affects flowering.